EVANGELISATION AS THE JOYFUL EPIPHANY OF CHRISTIAN LIFE - Kochappilly, Paulachan (Asian Horizons, 2011)
As the Syro-Malabar Church of the Saint Thomas Christians of India celebrates the Mission Year marking the golden jubilee of the Chanda mission, it is appropriate to review, revive, and renew the missionary vocation of the Church. The Church, “the universal sacrament of salvation (LG 48), is missionary by her very nature” (AG 2). It is to be recalled that “missionary activity is nothing else and nothing less than a manifestation or epiphany of God’s will and fulfilment of that will in the world and history” (AG 9; MP 1.5). The Church is a covenant community, an ecclesial community, the Mystical Body of Christ. The Church is a communion of persons in Christ through the Spirit oriented towards the glory of God and the flourishing of people on earth. It is a communion of the members of the Mystical Body of Christ. So whatever one does is done in the name of all others. The Church “exists in order to evangelise” (EN 14). “Evangelisation is not an individual act; it is one that is deeply ecclesial” (EN 60). It is a great joy and a responsibility that the members undertake in the name of the Church. “Woe to me if I do not preach the Gospel” (1 Cor 9:16). As a member of the Church, I, too, share the Good News of the Lord in order that my joy may be in others and their joy may be complete.